1999
DOI: 10.1046/j.1365-2958.1999.01605.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Escherichia coli cell division genes ftsA and ftsZ by the two‐component system rcsC–rcsB

Abstract: SummaryGenes rcsC and rcsB form a two-component system in which rcsC encodes the sensor element and rcsB the regulator. In Escherichia coli, the system positively regulates the expression of the capsule operon, cps, and of the cell division gene ftsZ. We report the identi®cation of the promoter and of the sequences required for rcsB-dependent stimulation of ftsZ expression. The promoter, ftsA1p, located in the ftsQ coding sequence, co-regulates ftsA and ftsZ. The sequences required for rcsB activity are immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
120
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 36 publications
1
120
0
1
Order By: Relevance
“…Bacteria were grown on LB medium or M9 minimal salts medium containing 0.4 % glycerol (Miller, 1972;Sambrook & Russell, 2001 et al, 2004). A position-specific weight matrix was generated using RcsB-binding sites described by Wehland & Bernhard (2000), as well as RcsB-binding sequences identified in the promoters of flhDC, rprA, osmC and ftsZ genes in E. coli (Carballes et al, 1999; DavalosGarcia et al, 2001;Francez-Charlot et al, 2003;Majdalani et al, 2002). The sensitivity threshold was set to 0.8-11.3, only RcsB-binding sites within 350 bp of the start of translation were considered, and the search was restricted to intergenic regions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria were grown on LB medium or M9 minimal salts medium containing 0.4 % glycerol (Miller, 1972;Sambrook & Russell, 2001 et al, 2004). A position-specific weight matrix was generated using RcsB-binding sites described by Wehland & Bernhard (2000), as well as RcsB-binding sequences identified in the promoters of flhDC, rprA, osmC and ftsZ genes in E. coli (Carballes et al, 1999; DavalosGarcia et al, 2001;Francez-Charlot et al, 2003;Majdalani et al, 2002). The sensitivity threshold was set to 0.8-11.3, only RcsB-binding sites within 350 bp of the start of translation were considered, and the search was restricted to intergenic regions.…”
Section: Methodsmentioning
confidence: 99%
“…The Rcs phosphorelay has been implicated in the synthesis of virulence factors in Pcc and other plant-pathogenic bacteria and also in human pathogens (Hinchliffe et al, 2008;Mouslim et al, 2004;Wang et al, 2009Wang et al, , 2007. RcsB activates the biosynthesis of capsular exopolysaccharides, transcription of the cell division gene, ftsZ, transcription of a cell envelope protein, osmC, and transcription of RprA RNA to increase expression of the stationary-phase sigma factor, RpoS, in E. coli (Carballes et al, 1999;Davalos-Garcia et al, 2001;Gervais et al, 1992;Gottesman et al, 1985;Majdalani et al, 2002). Francez-Charlot et al (2003) demonstrated that the Rcs phosphorelay system represses motility through the direct binding of RcsB to the promoter of flhDC in E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the wza-wca gene cluster, targets regulated by the Rcs system with its cofactor RcsA include the motility master operon fhlDC (Francez-Charlot et al, 2003), rcsA and, in Salmonella, the gene ugd, which is required for the incorporation of 4-aminoarabinose into the lipopolysaccharide (Mouslim & Groisman, 2003). The cell division fts genes (Carballes et al, 1999), the osmoregulated osmC gene (Davalos-Garcia et al, 2001) and rprA, encoding a small RNA which stimulates the translation of the general stressresponse sigma factor RpoS (Majdalani et al, 2002), are also controlled by RcsB, but independently of RcsA. Although RcsB acts preferentially as an activator, it negatively controls flhDC expression (Francez-Charlot et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The plasmid pHR758 was constructed by replacing the ampicillin resistance gene of pFZY1 (Koop et al, 1987) with the kanamycin resistance gene of pKC7 (Rao and Rogers, 1979). The 0.5 kb HincII fragment containing the promoter for the cps operon (P cps ) (Stout, 1996;Wehland and Bernhard, 2000) and the 1 kb BamHI-Bgl II fragment containing the promoter for ftsA and ftsZ (P ftsAZ ) (Carballès et al, 1999) were cloned into pHR758 to construct pHR770 and pHR771, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…They are the last two genes but one in the 16-gene cluster of cell division/cell envelope biosynthesis genes, which has a complex transcriptional organization with multiple promoters (Joseleau-Petit et al, 1999). Among them, a promoter located just upstream of ftsA, P ftsAZ , has been shown to be positively regulated by RcsB, independently of RcsA (Carballès et al, 1999;Gervais and Drapeau, 1992). We initially suspected that ftsAZ hyperexpression due to the Rcs activation might be responsible for the growth defect of the pgsA null strain at 42°C.…”
Section: The Thermosensitive Defect Of the Pgsa Null Mutant At 42°c Dmentioning
confidence: 99%